(untitled) (Research, Society and Development, 2024)
This article aims to understand the historical trajectory of the construction of the Unified Health System (SUS) in Brazil, from its initial milestones to its consolidation as a public health policy. The research seeks to analyze the political, social, and economic processes that contributed to the creation and evolution of SUS, highlighting the main legal and institutional milestones over time. A qualitative and descriptive approach was adopted, based on widely recognized theoretical and methodological principles in the scientific literature. The methodology allowed for an in-depth analysis of the main historical events, the transformations of SUS, and the role of various social and political actors who influenced the health system over the decades. The results point to the evolution of SUS, with emphasis on essential legal milestones such as Laws 8.080/1990 and 8.142/1990, which defined the system’s organizational structure and its decentralization. Significant advances were identified, such as the expansion of access to health and the creation of programs like the Family Health Strategy, but persistent challenges also emerged, such as system underfunding, regional inequalities, and lack of adequate resources. The study contributes to understanding the victories and limitations of SUS and provides insights for reflection on its contemporary and future challenges.